Denominational Correlates of Changing Religious Beliefs in College - Burchard, Waldo W. (Sociological analysis, 1970)
This report, based on data from a study of the effects of college education on religious beliefs and behavior, analyzes the responses, by religious membership (Catholic and Protestant) of 106 women and 66 men who as freshmen and again as seniors responded to identical items in a questionnaire dealing with religious and moral beliefs. Ten items for men and eleven items for women (from a total of 73) were selected for this analysis. Responses to all items show that there has been a change toward more liberal beliefs for men and women, Catholics and Protestants, although in general Catholic responses are more conservative than Protestant. Responses for Catholic men exhibit a pattern—although vague—which appears to be related to their religious membership. No such pattern appears in the responses of Protestant men or in those of either Catholic or Protestant women. Although a religious differential is apparent in the responses, the data at hand do not reveal the nature of its influence.